Does physical activity increase or decrease the risk of sickle cell disease complications?. Issue 4 (23rd December 2015) - Martin, Cyril; Pialoux, Vincent; Faes, Camille; Charrin, Emmanuelle; Skinner, Sarah; Connes, Philippe
Abstract : Sickle cell disease (SCD) is the most common inherited disease in the world. Red blood cell sickling, blood cell-endothelium adhesion, blood rheology abnormalities, intravascular haemolysis, and increased oxidative stress and inflammation contribute to the pathophysiology of SCD. Because acute intense exercise may alter these pathophysiological mechanisms, physical activity is usually contra-indicated in patients with SCD. However, recent studies in sickle-cell trait carriers and in a SCD mice model show that regular physical activity could decrease oxidative stress and inflammation, limit blood rheology alterations and increase nitric oxide metabolism. Therefore, supervised habitual physical activity may benefit patients with SCD. This article reviews the literature on the effects of acute and chronic exercise on the biological responses and clinical outcomes of patients with SCD.